2021
DOI: 10.1158/2326-6066.cir-20-0445
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Adrenergic Stress Contributes to Metabolic Dysfunction and an Exhausted Phenotype in T Cells in the Tumor Microenvironment

Abstract: Synopsis: T-cell exhaustion impacts immunotherapy efficacy. How T-cell exhaustion is regulated remains incompletely understood. Here, the sympathetic stress response is shown to regulate the development of T-cell exhaustion by modulating CD8 + T-cell metabolism and function in the TME.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 54 publications
(92 reference statements)
0
57
0
Order By: Relevance
“…Endogenous glucocorticoid signaling led to dysfunctional CD8+ T cells characterized by increased expressions of PD-1, TIM-3, and Lag3 (Acharya et al, 2020). Stress-induced β-AR activation suppressed T-cell receptor (TCR) signaling in a rodent melanoma model and a rodent colon cancer model (Qiao et al, 2021). β2-AR activations in regulatory T (Treg) cells increased their immunosuppressive functions associated with decreased interleukin (IL-2) level and improved differentiation of CD4+ Foxp3-T cells into Foxp3+ Tregs in a rodent model (Guereschi et al, 2013).…”
Section: Immune Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endogenous glucocorticoid signaling led to dysfunctional CD8+ T cells characterized by increased expressions of PD-1, TIM-3, and Lag3 (Acharya et al, 2020). Stress-induced β-AR activation suppressed T-cell receptor (TCR) signaling in a rodent melanoma model and a rodent colon cancer model (Qiao et al, 2021). β2-AR activations in regulatory T (Treg) cells increased their immunosuppressive functions associated with decreased interleukin (IL-2) level and improved differentiation of CD4+ Foxp3-T cells into Foxp3+ Tregs in a rodent model (Guereschi et al, 2013).…”
Section: Immune Cellsmentioning
confidence: 99%
“…β-blockers, such as propranolol and metoprolol, can block the interactions between catecholamine and β-AR, which inhibits the subsequent cancer-promoting effects induced by β-AR signaling as mentioned above (Fumagalli et al, 2020). Blocking β-AR interrupts the differentiation of exhausted T progenitors and decreases the number of exhausted T cells in TME (Qiao et al, 2021). Propranolol reduced MDSC accumulation in the TME of thermal-stressed mice treatments and controlled tumor growth (MacDonald et al, 2021).…”
Section: Anti-cancer Treatments and Interventions Targeting Chronic Stress β-Blockermentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, while impairing MDSC function, β-blockers significantly improve the function of effector CD8 T cells ( Qiao et al, 2019 ). We recently showed that using propranolol as a β-blocking agent significantly improves the metabolic fitness of T cells by increasing glycolysis and decreasing T cell exhaustion, indicating that β2-AR signaling has different metabolic effects on unique immune cell types ( Qiao et al, 2021 ). In addition, MDSCs use different immunosuppressive tools, including the production of arginase-I, the release of nitric oxide (NO), PGE2, and peroxynitrite (PNT), and the expression of programmed cell death protein-ligand 1 (PD-L1), depending on the type of cancer ( Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its effects on obesity models, housing mice at thermoneutrality vs. standard temperature has been shown to change the outcome in experiments using mouse models of nonalcoholic fatty liver disease [47], asthma [48], oral antigen sensitization [49], obesity and inflammation [50], osteoporosis [51], infection [52], atherosclerosis [53], and immune responses (LPS) [50]. Our lab has reported that cool ambient temperature, and the resultant adrenergic stress response, promotes tumor growth [45,54,55], reduces response to chemotherapy and radiation [56,57] and immunotherapy [44], reduces the anti-tumor immune response [44,58], immune cell function [59][60][61][62], graft vs. host disease [63], and heat shock protein induction [64]. We have also found elevated levels of NE in blood and tumors of mice housed at standard temperature [44,45].…”
Section: Housing Conditions Cause Chronic Inadvertent Baseline Stressmentioning
confidence: 99%